2008
DOI: 10.1007/s00343-008-0035-2
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated dibenzo-p-dioxins (PCDDs) and dibenzofurans (PCDFs) in surface sediment and bivalve from the Changjiang Estuary, China

Abstract: Surface sediments and bivalves were collected from the Changjiang Estuary in December 2003 and November 2004, respectively. Polychlorinated dibenzo-p-dioxins (PCDDs) and dibenzofurans (PCDFs) in these samples were measured with high-resolution chromatography (HRGC)/High Resolution Mass Spectrometer (HRMS). The concentrations of total PCDD/Fs and toxic equivalent (TEQ) were 169.83±119.63 and 0.81±0.36 pg/g dry weight (dw) in sediments, and 580.33±240.17 and 7.24±3.65 pg/g dw in bivalves. The homolog composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 38 publications
1
12
1
Order By: Relevance
“…PCP and its salts were used extensively for fighting against schistosomiasis and as pesticides in China in the last decades (Zhang et al 2001;Schecter et al 1994), resulting in wide occurrence of PCP at relatively high concentrations in aquatic environment (Yan et al 2005;Ling and Gao 2004;Fang et al 2008;Wen et al 2008). PCP contamination level of sediments in China reported before indicated that it is more severe than that in many other countries (Ling and Gao 2004;Qi et al 2007;Kobayashi et al 2008;Dmitruk and Piascik 2008).…”
Section: Introductionmentioning
confidence: 94%
“…PCP and its salts were used extensively for fighting against schistosomiasis and as pesticides in China in the last decades (Zhang et al 2001;Schecter et al 1994), resulting in wide occurrence of PCP at relatively high concentrations in aquatic environment (Yan et al 2005;Ling and Gao 2004;Fang et al 2008;Wen et al 2008). PCP contamination level of sediments in China reported before indicated that it is more severe than that in many other countries (Ling and Gao 2004;Qi et al 2007;Kobayashi et al 2008;Dmitruk and Piascik 2008).…”
Section: Introductionmentioning
confidence: 94%
“…This huge amount of sediment is one of the major factors affecting the balance of sedimentary and ecological environments in the Bohai Sea, Yellow Sea and East China Sea (Zhang 1999). Although there were a few investigations on levels of PCDD/Fs or PCBs in surface sediments from Yangtze Estuary (Liu et al 2003;Wen et al 2008), there were little information about PCDD/Fs and PCBs in surface sediments in Yellow Estuary. The present study aimed to investigate the levels of PCDD/Fs and dl-PCBs and discuss the spatial distributions and potential sources in these two estuaries.…”
mentioning
confidence: 99%
“…With regard to DL-PCBs, it can be assumed that they were within the permissible level based on the TEQ values obtained. These levels were relatively low compared with those measured in other estuaries and coastal areas around the world, such as Yangtze River Estuary (Wen et al, 2008) and Spanish Coast (Eljarrat et al, 2005) (Table 3). The distribution of WHO-TEQ values for DL-PCBs was a little different from that of concentrations due to the contribution otherness of specific compounds to the WHO-TEQ.…”
Section: Toxic Equivalents (Teqs) Of Pcdd/fs and Dl-pcbsmentioning
confidence: 57%
“…Over the past few years, many studies focusing on PCDD/Fs or DL-PCBs have been conducted in different coastal sea areas and estuaries around the world (Birch et al, 2007;Howell et al, 2011;Ishaq et al, 2009;Kannan et al, 2007;Salo et al, 2008;Sundqvist et al, 2010;Verta et al, 2007). In China, studies have been carried out for estuaries such as the Yellow River Estuary (Hui et al, 2009), Yangtze River Estuary (Hui et al, 2009;Wen et al, 2008), Pearl River Delta (Zhang et al, 2009) and other coastal sea areas such as Hong Kong (Mũller et al, 2002), Bohai Bay (Hu et al, 2005), Jiaozhou Bay (Pan et al, 2008) and the Yellow Sea (Pan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%